The ITALK Project: A Developmental Robotics Approach to the Study of Individual, Social, and Linguistic Learning. (17th June 2014) - Broz, Frank; Nehaniv, Chrystopher L.; Belpaeme, Tony; Bisio, Ambra; Dautenhahn, Kerstin; Fadiga, Luciano; Ferrauto, Tomassino; Fischer, Kerstin; Förster, Frank; Gigliotta, Onofrio; Griffiths, Sascha; Lehmann, Hagen; et al.
Abstract This article presents results from a multidisciplinary research project on the integration and transfer of language knowledge into robots as an empirical paradigm for the study of language development in both humans and humanoid robots. Within the framework of human linguistic and cognitive development, we focus on how three central types of learning interact and co‐develop: individual learning about one's own embodiment and the environment, social learning (learning from others), and learning of linguistic capability. Our primary concern is how these capabilities can scaffold each other's development in a continuous feedback cycle as their interactions yield increasingly sophisticated competencies in the agent's capacity to interact with others and manipulate its world. Experimental results are summarized in relation to milestones in human linguistic and cognitive development and show that the mutual scaffolding of social learning, individual learning, and linguistic capabilities creates the context, conditions, and requisites for learning in each domain. Challenges and insights identified as a result of this research program are discussed with regard to possible and actual contributions to cognitive science and language ontogeny. In conclusion, directions for future work are suggested that continue to develop this approach toward an integrated framework for understanding these mutually scaffolding processes as a basis for language development in humans and robots.